Customary Sanctions from the Perspective of 'Urf: Cancellation of Engagement According to the Customary Leaders of Langsa City - Muharrani (International Journal of Sharia Studies, 2023)
The people of Langsa City impose customary sanctions for couples who cancel their engagement by returning the gold if the woman cancels and forfeiting the gold if the man cancels. This research aims to look at the theory of 'Urf on the customary sanctions imposed by the customary leaders of Langsa City. This research method is empirical law with a qualitative approach, what is meant by empirical law is the legal behavior of the community which is a social symptom that is not written, the source of empirical legal research data does not rely on written positive law but the results of observations at the research location. The results showed that the Urf theory and the value of the benefit that is trying to be maintained in the customary sanctions imposed on the party who canceled the engagement. Then it is appropriate and does not contradict anything. This is reinforced by the elimination of the return of double fines from the woman's side.